The Relationship between the Highest Prices and Trading Volume in the Share Indices of Energy and Oil Companies in Kazakhstan - Zhussipova, Elmira Y.; Ydyrys, Serikbay Saduakasuly; Makhanbetova, Ulmeken; Tayauova, Gulzhanat; Pirmanova, Zhansulu (International Journal of Energy Economics and Policy, 2023)
This study uses econometric methods to reveal the relationship between the highest price formation and trading volume in the share indices of energy and oil companies traded on the Kazakhstan Stock Exchange (KASE). The study used daily transaction data of KEGC, KZAP, and KZTO companies for 200 trading days in 2022. The analysis is based on the VAR method. The shock effect analysis concluded that there is a mutual interaction between the trading volume and the highest price formation for all three companies. Trading volume had a causal effect on the highest price of only one company (KZTO). The existence of a correlation between the trading volume and the highest price formation is important for investment decisions. This can be interpreted as an indication of a connection between the trading volume and the highest price formation in KASE. More information on this relationship can be obtained by performing similar analyses for other companies traded in the KASE.